Multilocus variable-number tandem repeat analysis for molecular typing and phylogenetic analysis of Shigella flexneri - Wang, You-Wun (BioMed Central, 2009)
BACKGROUND: Shigella flexneri is one of the causative agents of shigellosis, a major cause of childhood mortality in developing countries. Multilocus variable-number tandem repeat (VNTR) analysis (MLVA) is a prominent subtyping method to resolve closely related bacterial isolates for investigation of disease outbreaks and provide information for establishing phylogenetic patterns among isolates. The present study aimed to develop an MLVA method for S. flexneri and the VNTR loci identified were tested on 242 S. flexneri isolates to evaluate their variability in various serotypes. The isolates were also analyzed by pulsed-field gel electrophoresis (PFGE) to compare the discriminatory power and to evaluate the usefulness of MLVA as a tool for phylogenetic analysis of S. flexneri. RESULTS: Thirty-six VNTR loci were identified by exploring the repeat sequence loci in genomic sequences of Shigella species and by testing the loci on nine isolates of different subserotypes. The VNTR loci in different serotype groups differed greatly in their variability. The discriminatory power of an MLVA assay based on four most variable VNTR loci was higher, though not significantly, than PFGE for the total isolates, a panel of 2a isolates, which were relatively diverse, and a panel of 4a/Y isolates, which were closely-related. Phylogenetic groupings based on PFGE patterns and MLVA profiles were considerably concordant. The genetic relationships among the isolates were correlated with serotypes. The phylogenetic trees constructed using PFGE patterns and MLVA profiles presented two distinct clusters for the isolates of serotype 3 and one distinct cluster for each of the serotype groups, 1a/1b/NT, 2a/2b/X/NT, 4a/Y, and 6. Isolates that had different serotypes but had closer genetic relatedness than those with the same serotype were observed between serotype Y and subserotype 4a, serotype X and subserotype 2b, subserotype 1a and 1b, and subserotype 3a and 3b. CONCLUSIONS: The 36 VNTR loci identified exhibited considerably different degrees of variability among S. flexneri serotype groups. VNTR locus could be highly variable in a serotype but invariable in others. MLVA assay based on four highly variable loci could display a comparable resolving power to PFGE in discriminating isolates. MLVA is also a prominent molecular tool for phylogenetic analysis of S. flexneri; the resulting data are beneficial to establish clear clonal patterns among different serotype groups and to discern clonal groups among isolates within the same serotype. As highly variable VNTR loci could be serotype-specific, a common MLVA protocol that consists of only a small set of loci, for example four to eight loci, and that provides high resolving power to all S. flexneri serotypes may not be obtainable.